Nasopharyngeal cancer detection based on blood plasma surface-enhanced Raman spectroscopy and multivariate analysis - Feng, Shangyuan; Chen, Rong; Lin, Juqiang; Pan, Jianji; Chen, Guannan; Li, Yongzeng; Cheng, Min; Huang, Zufang; Chen, Jiesi; Zeng, Haishan (Biosensors & bioelectronics, 2010)
A surface-enhanced Raman spectroscopy (SERS) method was developed for blood plasma biochemical analysis for the first time with the aim to develop a simple blood test for non-invasive nasopharyngeal cancer detection. Silver nanoparticles (Ag NP) as the SERS-active nanostructures were directly mixed with blood plasma to enhance the Raman scattering signals of various biomolecular constituents such as proteins, lipids, and nucleic acids. High quality SERS spectrum from blood plasma–Ag NP mixture can be obtained within 10 s using a Renishaw micro-Raman system. SERS measurements were performed on two groups of blood plasma samples: one group from patients ( n = 43) with pathologically confirmed nasopharyngeal carcinomas (WHO type I, II, and III) and the other group from healthy volunteers (control subjects, n = 33). Tentative assignments of the Raman bands in the measured SERS spectra suggest interesting cancer specific biomolecular differences, including an increase in the relative amounts of nucleic acid, collagen, phospholipids and phenylalanine and a decrease in the percentage of amino acids and saccharide contents in the blood plasma of nasopharyngeal cancer patients as compared to that of healthy subjects. Principal component analysis (PCA) of the measured SERS spectra separated the spectral features of the two groups into two distinct clusters with little overlaps. Linear discriminate analysis (LDA) based on the PCA generated features differentiated the nasopharyngeal cancer SERS spectra from normal SERS spectra with high sensitivity (90.7%) and specificity (100%). The results from this exploratory study demonstrated great potentials for developing SERS blood plasma analysis into a novel clinical tool for non-invasive detection of nasopharyngeal cancers.